2021
DOI: 10.1101/2021.05.25.21257799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating LIGHT (TNFSF14) and Interleukin-18 Levels in Sepsis-Induced Multi-Organ Injuries

Abstract: Objective The cytokines, LIGHT (TNFSF14) and Interleukin-18 (IL-18), are two important therapeutic targets due to their central roles in the function of activated T cells and inflammatory injury. LIGHT was recently shown to play a major role in COVID19 induced acute respiratory distress syndrome (ARDS), reducing mortality and hospital stay. This study aims to investigate the associations of LIGHT and IL-18 with non-COVID19 related ARDS, acute hypoxic respiratory failure (AHRF) or acute kidney injury (AKI), se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 87 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…To identify the NAFLD patients showing impaired performance in each parameter measured by these tests, we applied the mean ± 2 SD criterion [21,[27][28][29], calculating the mean and SD of the value for each parameter for the control group and adding or subtracting twice the SD to this mean to obtain a cutoff (see Table 2). This cutoff was applied to assess which parameters show impaired performance in each patient.…”
Section: Procedures To Classify Nafld Patients As With or Without Mild Cognitive Impairment (Mci/nmci)mentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the NAFLD patients showing impaired performance in each parameter measured by these tests, we applied the mean ± 2 SD criterion [21,[27][28][29], calculating the mean and SD of the value for each parameter for the control group and adding or subtracting twice the SD to this mean to obtain a cutoff (see Table 2). This cutoff was applied to assess which parameters show impaired performance in each patient.…”
Section: Procedures To Classify Nafld Patients As With or Without Mild Cognitive Impairment (Mci/nmci)mentioning
confidence: 99%
“…Patients whose parameter score was within the range of the mean ± 2 SD were classified as without impairment and those falling outside this range were classified as having impaired performance for this parameter. This criterion has been previously used to identify patients with impaired performance in psychometric tests [21] and also to identify data outside the normal range in many other types of studies [27][28][29]. We used these data to design a new method to classify patients as with MCI or without MCI (NMCI) by developing a new score, as described in the results section.…”
Section: Procedures To Classify Nafld Patients As With or Without Mild Cognitive Impairment (Mci/nmci)mentioning
confidence: 99%
“…10 Clinical studies have shown that patients with sepsis-induced ARDS phenotype are more severely ill than non-sepsis-related ARDS patients, have poorer recovery from lung injury, lower extubation success rates, higher short-term mortality, and poor long-term prognosis. 11,12 Due to the complex and diverse mechanism of exogenous lung injury in sepsis, the exact mechanism is not fully understood. However, studies have indicated that autophagy plays an important role in the occurrence and development of sepsis-induced ARDS by regulating the levels of pro-and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed distinct differences in clinical characteristics, molecular mechanisms and treatment responses among the ARDS subtypes 10 . Clinical studies have shown that patients with sepsis‐induced ARDS phenotype are more severely ill than non‐sepsis‐related ARDS patients, have poorer recovery from lung injury, lower extubation success rates, higher short‐term mortality, and poor long‐term prognosis 11,12 . Due to the complex and diverse mechanism of exogenous lung injury in sepsis, the exact mechanism is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Qu et al. suggests that LIGHT plays a role in viral and bacterial sepsis induced acute respiratory distress syndrome (ARDS) ( 53 ). From a cohort of 280 patients, in the bacterial sepsis cases (n=189), significantly elevated LIGHT was associated with ARDS, higher Apache III scores, acute kidney injury (AKI), and acute hypoxic respiratory failure (AHRF).…”
Section: Light : Hvem/ltβr/dcr3mentioning
confidence: 99%